Expression and function assessment of two serpin-type serine protease inhibitors from Haemaphysalis doenitzi. (October 2020) - Du, Wenjing; Gao, Zhihua; Wang, Kuang; Zhao, Yinan; Zheng, Peijing; Yu, Zhijun; Liu, Jingze; Yang, Xiaolong
Abstract: Serine protease inhibitors (serpins) in ticks are implicated in the modulation of the vertebrate host response to the tick bite. Experimentally, it has been demonstrated that serpins interfere with tick-borne pathogen transmission. However, knowledge on serpins in the tick Haemaphysalis doenitzi is lacking. In this study, the expression of two serpin genes, named HDS1 and HDS2, were assessed in H. doenitzi, and their roles in immune regulation were further investigated. The expression of HDS1 and HDS2 showed no tissue specificity, with maximum expression levels detected in the hemolymph and salivary gland, respectively. Among the developmental stages, the highest expression of HDS1 and HDS2 were detected in larvae and adults, respectively. The recombinant protein rHDS1 displayed obvious inhibitory effects on trypsin and thrombin, whereas rHDS2 clearly inhibited thrombin only. In addition, rHDS1 and rHDS2 showed certain inhibitory activities against bacteria and fungi. The female engorgement body weight, female engorgement rate, and egg hatchability were significantly decreased after injection of double-stranded RNA (dsRNA) of HDS1 gene, whereas no significant effects were observed concerning the feeding period or attachment rate at 24 h after introduction via rabbit ears. When injected with dsRNA of HDS2 gene, no significant effect was observed on the attachment rate at 24 h after introduction into the rabbit ears, but the engorgement body weight and engorgement rate of female ticks were significantly decreased, and no egg hatchment occurred. The above results contribute to better understanding the function of serpins in the development and innate immunity of H. doenitzi . Highlights: Two Serpin-type serine protease inhibitors genes, named HDS1 and HDS2, were characterized and assessed in Haemaphysalis doenitzi . The expression of HDS1 and HDS2 showed no tissue specificity. The recombinant proteins displayed obvious inhibitory effects on thrombin, and certain inhibitory activities against bacteria and fungi. Both HDS1 and HDS2 play important roles in development and immune regulation of H. doenitzi .